Pengembangan Soal Serupa Timss Untuk Mengukur Kemampuan Pemecahan Masalah Pada Konten Geometri Kelas VIII - Setiawan, Ari; Prof.Dr. Budi Murtiyasa, Prof.Dr. Budi Murtiyasa M.Kom (2017)
This study aims to produce about TIMSS field Geometry valid and practical. This research used research and development method. The method used in this research is the development of research methods. This study requires ostages:preliminary and formative stages of evaluation that includes self evaluation, expert reviews, one-to-one, small group, and a field test. Data collection techniques used by walktrough, document, test, and interview. The test results overall of the problem solving skill at the stage of field test is six students (24%) fine, fifthteen students (60%) good, four students (16%) fair. The test results obtained by the average value of problem solving skill 7,03, included in the category of good. However, these results can also be said that a similar problem developed TIMSS considered valid and practical criteria and have a potential effect on students' mathematical problem solving skill.Keywords: geometry, math, problem solving skill, TIMSS